Case Report: An Unusual Case of Fasciculoventricular Pathway - Yang, Liu; Chen, Zhijian; Zhang, Min (Frontiers in Cardiovascular Medicine, 2022)
A 30-year-old man with an electrocardiogram (ECG) demonstrating ventricular preexcitation with a normal PR interval as well as a QR pattern in the Lead V1 was evaluated. Electrophysiology studies showed a normal AH interval and a shortened HV interval at sinus rhythm; while the degree of preexcitation (QRS waveform) and HV interval were not affected by multisite or incremental atrial pacing. These findings implied ventricular preexcitation due to a fasciculoventricular pathway (FVP). Moreover, temporarily blocking the FVP conduction mechanically resulted in a normal HV interval, absence of delta wave and a rSR’ pattern in V1, which indicated incomplete right bundle branch block (IRBBB). These findings suggested the coexistence of FVP and IRBBB, which is very rare.